Desenvolvimento de um simulador de coletor solar para reprodução das condições de operação de uma bomba de calor para aquecimento de água residencial - Oscar Ricardo Sandoval Rodriguez (2015)
With the increased demand for renewable energy, the use of solar energy has been widely studied. Brazil is a privileged country, considering the high levels of solar radiation received in almost all the national territory. However, there are days that there is a deficit in solar energy, because the day is cloudy or rainy. Therefore, solar collectors need an additional energy source to contribute to the heating of the water until the desired temperature is reached. In this work is presented the experimental study of a heat pump working with R-134a, as a device to support a solar collector for heating water in the city of Belo Horizonte -MG. To simulate the operation of the system, it was employed a set of electrical resistances for simulating historical values of annual solar radiation. This study revealed that only in January the use of solar energy is enough to reach the temperature of 45°C in the reservoir, and the other eleven months it is necessary to use the heat pump to achieve that temperature. With the heat pump operating close to the real conditions the coefficient of performance obtained was 1.88, an average annual consumption of 137.65 kWh with a cost of R $ 54.57. Finally, the results show that by this method it is possible to develop reliable solar simulators in order to study the behavior and characteristics of new support systems for solar collectors.